The influence of the concept of ‘taklif’ to accountants in preventing fraudulent financial reporting and auditing / Nawal Kasim and Nurul Khairiyah Khalid. - Kasim, Nawal; Khalid, Nurul Khairiyah (Universiti Teknologi MARA Cawangan Selangor, 2010)
The current role of accountants is limited to compliance with rules and procedures and completeness of paperwork. It is easy to show that an organisation can comply with all rules and regulations without realizing that the financial reporting and auditing are fraudulent. Therefore, the function is inadequate for an Islamic society with a very heavy social and ethical agenda. The current paper argues that Islam has indirectly laid down a key concept in accounting i.e. “taklif” or “accountability” in one of its surah in the al-Quran i.e. Al-Baqarah, verse 282 (2:282). The objective of this paper is to examine the values embedded behind this surah that would set a conceptual framework for future research investigating how accountability in Islam is realised into actual practice.